A Treatment on Pregnant Mothers Infected With Covid-19: A Scoping Review - Rusdi, Annisa; Sulistyaningsih, Sulistyaningsih; Kurniawati, Herlin Fitriana (Universitas Aisyah Pringsewu, 2021)
The 2019 coronavirus disease outbreak has become a threat to at-risk groups, one of which is pregnant mothers. Immunocompromised status and physiological adaptive changes make them more susceptible to infection. This review aims to determine the treatment of pregnant mothers infected with COVID-19. The researchers conducted a scoping review that adapted the Arksey and O'Malley framework through databases from PubMed, EBSCO and ProQuest. They found 25 out of 3244 articles that were selected based on inclusion and exclusion criteria. The treatment of pregnant mothers infected with COVID-19 is described in four themes. First, the process of diagnosing COVID-19 with RT-PCR examination, abdominal CT-scan, and an assessment of medical history and clinical symptoms. After that, the procedure of antenatal treatment is done by forming a multidisciplinary team, classifying pregnant women, determining the location of care, giving oxygen therapy, conducting laboratory examinations, administering treatment therapy, and determining the conditions for returning patients who are declared free from COVID-19. Furthermore, delivery management by minimizing labor and delivery support staff, determining the right delivery room, determining the delivery method according to medical indications, anaesthesia and COVID-19 is not an indication for termination of pregnancy. Lastly, postpartum treatment by isolating mother and her baby, checking vertical transmission, considering breastfeeding and providing psychological support. The researchers suggest to carry out further studies on safe medical therapy, appropriate delivery methods and the risk of vertical transmission between mother and her baby.Wabah penyakit coronavirus 2019 telah menjadi ancaman bagi kelompok berisiko seperti wanita hamil. Status immunocompromised dan perubahan adaptif fisiologis menyebabkan wanita hamil lebih rentan terhadap infeksi. Review ini bertujuan untuk mengetahui penatalaksanaan ibu hamil yang terinfeksi COVID-19. Scoping review mengadaptasi framework Arksey dan O’Malley, menggunakan database dari PubMed, EBSCO dan ProQuest. Ditemukan sebanyak 25 artikel dari 3244 yang diseleksi berdasarkan kriteria inklusi dan ekslusi. Penatalaksanaan kehamilan dengan infeksi COVID-19 digambarkan dalam empat tema. Diagnosis COVID-19 dengan pemeriksaan RT-PCR, CT-scan dada, penilaian riwayat kesehatan dan gejala klinis. Penatalaksanaan antenatal dengan membentuk tim multidisiplin, mengklasifikasikan ibu hamil, menentukan lokasi perawatan, pemberian terapi oksigen, pemeriksaan laboratorium, pemberian terapi pengobatan dan penentuan syarat kepulangan pasien yang dinyatakan bebas dari COVID-19. Penatalaksanaan persalinan dengan meminimalkan staf dan pendukung persalinan, menentukan ruang persalinan yang tepat, menentukan metode persalinan sesuai indikasi medis, anestesi dan COVID-19 bukan indikasi terminasi kehamilan. Penatalaksanaan postpartum dengan mengisolasi ibu dan bayi, melakukan pemeriksaan transmisi vertikal, pertimbangan menyusui dan memberikan dukungan psikologis. Diperlukan studi lebih lanjut mengenai terapi pengobatan yang aman, metode persalinan yang tepat dan resiko tranmisi vertikal antara ibu dan bayi.